2019
DOI: 10.1021/acs.jced.9b00542
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Thermodynamic Parameters of Amitriptyline Hydrochloride in Polar Organic Solvent–Water Mixed Media

Abstract: Organic solvent–water mixed media find applications in industrial, chemical, and pharmaceutical areas. This work discusses the micellization and related parameters such as degree of counterion dissociation (α), change in Gibbs energy of micellization (ΔG m 0) of an amphiphilic drug amitriptyline hydrochloride (AMT), and Gordon parameter (G p) in three polar organic solvents, viz., ethanol (EtOH), ethylene glycol (EG), and glycerol (GL)–water mixed media, with a special focus on the effects of a wide range of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The Gibbs free energy (Δ G m ° ) of micellization reveals the change in free energy once an amphiphilic monomer is transferred from the bulk solution to the micelle form . Devoting to the model of pseudophase separation, the Δ G m ° for amphiphiles can be determined by considering the g value of the ions to the micelle: In eq , X cmc is the cmc value in the mole fraction unit and R is the gas constant. The Δ G m ° values obtained were all negative for individual and mixtures of components in all studied solvents (Table ), showing that micellization in IH, NaT, and IH–NaT mixtures is significantly spontaneous in characteristics along with their negative values increasing with increase in the concentration of NaT in solution mixtures, confirming that mixture spontaneity increases as well as becomes thermodynamically more stable. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…The Gibbs free energy (Δ G m ° ) of micellization reveals the change in free energy once an amphiphilic monomer is transferred from the bulk solution to the micelle form . Devoting to the model of pseudophase separation, the Δ G m ° for amphiphiles can be determined by considering the g value of the ions to the micelle: In eq , X cmc is the cmc value in the mole fraction unit and R is the gas constant. The Δ G m ° values obtained were all negative for individual and mixtures of components in all studied solvents (Table ), showing that micellization in IH, NaT, and IH–NaT mixtures is significantly spontaneous in characteristics along with their negative values increasing with increase in the concentration of NaT in solution mixtures, confirming that mixture spontaneity increases as well as becomes thermodynamically more stable. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…From previous findings, it is known that self-assembling characteristics 48 of ionizable amphiphilic drug molecules gave an oblate spheroidal shape, which can even be explored in polar organic solvent. 49 Mixed micelle formation of amphiphilic drug 50,51 and its phase separation 52 is also reported, and keeping all these facts in mind, we envision it to be used for recovery of an antidepressant from pharmaceutical wastes. 53 Perusal of the literature revealed that selective AMT extraction−detection from an environmental matrix using microextraction using supramolecular solvents (SUPRAS) has not yet been explored.…”
Section: ■ Introductionmentioning
confidence: 86%
“…Supramolecular solvent-based microextraction , is the primary step for water detoxification from organic pollutants in an aqueous solution. From previous findings, it is known that self-assembling characteristics of ionizable amphiphilic drug molecules gave an oblate spheroidal shape, which can even be explored in polar organic solvent . Mixed micelle formation of amphiphilic drug , and its phase separation is also reported, and keeping all these facts in mind, we envision it to be used for recovery of an antidepressant from pharmaceutical wastes .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of 10% of GL & 15% of EG raises the value of α slightly but not in a regular trend. 81 The critical micelle concentration (CMC) and cloud point (CP) values of the solution rise with the addition of solvents, with ethyl glycol–water (EG–WR) mixed media showing a more dramatic impact than glycerol (GL–WR) mixed media. The increased electrostatic repulsion between the drug-micelle head groups, accomplished by lowering the permittivity of the mixed fluids, is responsible for the increase in values.…”
Section: Effect Of External Parameters On Drugs–surfactants Interactionmentioning
confidence: 99%